2018
DOI: 10.1089/3dp.2017.0043
|View full text |Cite
|
Sign up to set email alerts
|

The Value of 3D Printed Models in Understanding Acetabular Fractures

Abstract: Acetabular fractures are complex and difficult to classify. Although the Judet-Letournel classification is designed to increase the understanding of acetabular fractures, it remains prone to error when using conventional medical imaging. We hypothesize that three-dimensional (3D) printing, as a new diagnostic imaging tool, will lead to an increased understanding and knowledge of acetabular fractures and an optimal surgical approach. Digital data (DICOM) of 20 acetabular fractures were converted into 3D files [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 27 publications
2
34
1
6
Order By: Relevance
“… 18 Moreover, 3-D-printed pelvic models are used as templates for fitting and precontouring conventional osteosynthesis plates before the actual surgical procedure. 18 , 19 , 20 , 21 Several case series indicate that the use of 3-D-printed models in pelvic surgery are associated with reduced blood loss and shorter operation time. 22 , 23 , 24 , 25 , 26 Although the reported use of prebent plates, adapted to printed 3-D–models, show some benefits, little data are available on whether 3-D–printed models improve the quality of the reduction.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Moreover, 3-D-printed pelvic models are used as templates for fitting and precontouring conventional osteosynthesis plates before the actual surgical procedure. 18 , 19 , 20 , 21 Several case series indicate that the use of 3-D-printed models in pelvic surgery are associated with reduced blood loss and shorter operation time. 22 , 23 , 24 , 25 , 26 Although the reported use of prebent plates, adapted to printed 3-D–models, show some benefits, little data are available on whether 3-D–printed models improve the quality of the reduction.…”
Section: Discussionmentioning
confidence: 99%
“…HTPLA by ProtoPasta, at the moment, is the only 3D printing filament capable of offering the easiness of printing of PLA combined with high temperature resistance. Finally, comparing to [12], our method diminishes the wastage of material since the model is printed in multiple pieces, minimizing the use of support pillars for unsupported areas. Furthermore, printing the model in multiple pieces speeds up the printing step.…”
Section: Discussionmentioning
confidence: 99%
“…Three dimensional printing of complex fracture patterns such as acetabular and calcaneal fractures has been shown to improve consistency in fracture classification and patient understanding of the fracture and surgical plan. 9 , 34 With the growing focus on minimizing patient harm and competency-based education, 3D printing has the potential to play a key role in the future of orthopaedic education.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that the use of 3D-printed models based on real patient imaging improve the inter-rater reliability of complex acetabular fracture classification compared to the use of radiographs and cross-sectional imaging alone. 9 , 10 The use of 3D printing also has many clinical applications, including pre-operative planning, 11 13 manufacturing of patient-specific instrumentation (PSI), 14 16 and the manufacture of case-specific implants (e.g. plates and arthroplasty components).…”
Section: Introductionmentioning
confidence: 99%